Influence of green catalyst on transesterification process using ultrasonic-assisted - Chuah, L.F. (Elsevier Ltd, 2016)
Expansion of biodiesel production through transesterification reaction is restricted on the highly corrosive catalyst that generates environmental pollution. An exploration towards an environment-friendly and cleaner catalyst using biomass waste has become an attractive research in recent years. The aim of this study is to investigate empty fruit bunch doped with potassium hydroxide as a heterogeneous solid base catalyst for transesterification of rubber seed oil with methanol in ultrasonic batch system. Catalyst preparation was done using incipient wetness impregnation method. Synthesised catalyst named empty fruit bunch-potassium hydroxide was characterised by Fourier Transform Infrared, X-ray Diffraction and BrunauerâEmmettâTeller. Maximum free fatty acid reduction of 97.6 via esterification in mechanical stirring reactor was attained using 2.5 wt. sulphuric acid and 12:1 methanol to oil molar ratio at 65 Â°C for 50 min. In the case of transesterification, saponification was formed under operating conditions of 15 wt. of synthesised catalyst and 15:1 methanol to oil molar ratio at 40 Â°C for 30 min. This study indicated that empty fruit bunch-potassium hydroxide as the catalyst in transesterification reaction was ineffectiveness when assisted by ultrasonic. Â© 2016 Elsevier Ltd